Ganluyin ameliorates DSS-induced ulcerative colitis by inhibiting the enteric-origin LPS/TLR4/NF-κB pathway. (10th May 2022) - Xiong, Taoxiu; Zheng, Xiang; Zhang, Ke; Wu, Hansong; Dong, Yingjie; Zhou, Fuchen; Cheng, Bingbing; Li, Linzi; Xu, Wanfeng; Su, Jie; Huang, Jiahui; Jiang, Zetian; et al.
Abstract: Ethnopharmacological relevance: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD), that is associated with a significantly increased risk of colon cancer. As a classic traditional Chinese medicine, Ganluyin (GLY) has a long history as an anti-inflammatory medication, but its impacts on UC has not been established. Aim of the study: This study aims to evaluate the protective effect and mechanism of GLY on a pathway involving enteric-origin lipopolysaccharide (LPS), toll-like receptor (TLR)4, and NF-κB in mice with dextran sulfate sodium (DSS)-induced UC. Materials and methods: After three weeks of intragastric administration of GLY, a UC model was induced in mice by administration of 4% DSS in drinking water for one week. The disease activity index (DAI) was measured, and histological staining was used to detect histopathological changes of colon. LPS content of the serum was measured by ELISA, and the expression of tight junction proteins and proteins related to TLR4/NF-κB pathway in colon were analyzed by immunohistochemistry or Western Blotting. The intestinal flora was analyzed by 16S rRNA sequencing. Results: GLY improved the histological pathological changes of DSS-induced UC, as assessed by DAI, colonic mucosal damage, inflammatory cell infiltration, and goblet cell and mucus reduction. GLY also protected the intestinal mucosal barrier by increasing the expression of the tight junction proteins, occludin, claudin-1, and ZO-1 and by reducing the serum LPS content and decreasing the expression of TLR4, MyD88, NF-κB, IL-6, IL-1β, and TNF-α proteins in colon. Analyses of the intestinal flora showed that GLY restored the homeostasis of the intestinal flora through increases in the abundance of Firmicutes and decreases in the abundance of Proteobacteria and Bacteroidetes, which is associated with the production of LPS. Conclusion: GLY might exert an anti-UC effect by improving the colonic mucosal barrier and inhibiting the enteric-origin LPS/TLR4/NF-κB inflammatory pathway, and restoring the homeostasis of the intestinal flora in UC mice. These discoveries lay a strong foundation for GLY as a UC treatment. Graphical abstract: Image 1 Highlights: The Ganluyin showed a protective effect on the colonic mucosal barrier. The Ganluyin regulated the intestinal flora of UC mice. The Ganluyin could regulated the enteric-origin LPS/TLR4/NF-κB inflammatory pathway.